Challenges toward participation in international production-business activities and benefit sharing of Vietnam - Long, Hoang Xuan; Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Participation in international production-business activities brings benefits for Vietnam. Our labor based contribution, however, produces for Vietnam the benefits inferior to the ones of many other nations. This disadvantage is experiencing an increasing trend in the close future due to impacts from Industrial Revolution IV where some developed nations have plans to take home production activities. Therefore Vietnam has no ways to avoid the needs of enhancing its endogenic capacities for management, science-technology and marketing. Code: 19090401